2022
DOI: 10.1038/s42004-022-00750-z
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase fragmentation of single heteroatom-incorporated Co5MS8(PEt3)6+ (M = Mn, Fe, Co, Ni) nanoclusters

Abstract: Functionalization of metal-chalcogenide clusters by either replacing core atoms or by tuning the ligand is a powerful technique to tailor their properties. Central to this approach is understanding the competition between the strength of the metal-ligand and metal-metal interactions. Here, using collision-induced dissociation of atomically precise metal sulfide nanoclusters, Co5MS8L6+ (L = PEt3, M = Mn, Fe, Co, Ni) and Co5-xFexS8L6+ (x = 1–3), we study the effect of a heteroatom incorporation on the core-ligan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In our previous study, we used collision-energy-resolved CID experiments of Co 5 MS 8 L 6 + (M = Mn, Fe, Co, or Ni) clusters to examine their relative stability toward ligand loss. We found that the cluster stability increases in the order Co 5 FeS 8 (L 1 ) 6 + < Co 5 MnS 8 (L 1 ) 6 + < Co 6 S 8 (L 1 ) 6 + ≈ Co 5 NiS 8 (L 1 ) 6 + , with Co 5 FeS 8 (L 1 ) 6 + being the least stable cluster . Based on the observed surface reactivity of the corresponding fragment ions generated by the removal of one ligand from each cluster, we conclude that less stable gas phase precursor ions such as Co 5 FeS 8 (L 1 ) 6 + generate more stable fragment ions that do not react efficiently on surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we used collision-energy-resolved CID experiments of Co 5 MS 8 L 6 + (M = Mn, Fe, Co, or Ni) clusters to examine their relative stability toward ligand loss. We found that the cluster stability increases in the order Co 5 FeS 8 (L 1 ) 6 + < Co 5 MnS 8 (L 1 ) 6 + < Co 6 S 8 (L 1 ) 6 + ≈ Co 5 NiS 8 (L 1 ) 6 + , with Co 5 FeS 8 (L 1 ) 6 + being the least stable cluster . Based on the observed surface reactivity of the corresponding fragment ions generated by the removal of one ligand from each cluster, we conclude that less stable gas phase precursor ions such as Co 5 FeS 8 (L 1 ) 6 + generate more stable fragment ions that do not react efficiently on surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the cluster stability increases in the order Co 5 FeS 8 (L 1 ) 6 + < Co 5 MnS 8 (L 1 ) 6 + < Co 6 S 8 (L 1 ) 6 + ≈ Co 5 NiS 8 (L 1 ) 6 + , with Co 5 FeS 8 (L 1 ) 6 + being the least stable cluster. 44 Based on the observed surface reactivity of the corresponding fragment ions generated by the removal of one ligand from each cluster, we conclude that less stable gas phase precursor ions such as Co 5 FeS 8 (L 1 ) 6 + generate more stable fragment ions that do not react efficiently on surfaces. Meanwhile, more stable precursor ions such as Co 6 S 8 (L 1 ) 6 + with Co 5 NiS 8 (L 1 ) 6 + generate more reactive fragments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tandem mass spectrometry is ideally suited for preparing reactive fragments of metal chalcogenide clusters using controlled ligand removal in the gas phase . Soft landing of mass-selected fragment ions onto surfaces provides insights into their reactivity. We have previously used this approach to examine the reactivity of the undercoordinated Co 5 MS 8 (PEt 3 ) 5 + (M = Co, Mn, Fe, and Ni) fragment ions on surfaces.…”
Section: Introductionmentioning
confidence: 99%